PENGEMBANGAN VIDEO TUTORIAL PRAKTIKUM KIMIA UMUM BERBASIS KEHIDUPAN SEHARI-HARI DI MASA COVID-19 - Dina Fitriyah (Jurusan Tarbiyah dan Pendidikan, 2021)
The learning process that has been carried out in the General Chemistry practicum course during the COVID-19 pandemic is felt to be less than optimal. Learning General Chemistry during the Covid-19 pandemic was carried out boldly for theoretical material. However, another big problem is how to carry out practicum activities without laboratory access during the Covid-19 pandemic. Practical video media based on daily life utilizing computer technology in learning through practicum activities. Utilization of science and technology (science and technology) as a means of supporting learning is one of the positive impacts in developing knowledge. With the practical video in learning activities that are equipped with a combination of images and sound, the material can be visualized so that students can practice concluding and knowing laboratory materials and tools. Therefore, a step is needed to design a video tutorial based on daily life so that students can still do practicum through zoom because the tools and practicum materials are designed that are easy for students to support. Based on research conducted on K09 class students of Chemical Education, Raja Ali Haji Tanjungpinang University, it can show that the activities and responses of students to daily life-based practicum video tutorials are very good. So that the video media tutorial for general chemistry practicum based on everyday life can be used in the learning process. Keywords: covid19; practice; general chemistry; video